Perceived Value Sebagai Mediator yang Mempengaruhi Loyalitas Pelanggan Driver GO-JEK - Muhammad Falah Baraja Zain; Sopiah Sopiah (Ekonomi Bisnis, 2020)
Customer loyalty is a main goal for the company. Customer loyalty is a consumer behavior that is realized, among others, buying services continuously, recommending services to others, and having competitor's offer retention. Some of the factors that cause customer loyalty are the quality of service provided by the company and consumer perceived value. So, companies must consider their service efforts given to consumers. Service is declared quality if it meets the customer's needs and expectations. Increasing service quality will also affect consumer perceived value and customer loyalty. The objectives of this study include (1) explaining the requirements regarding service quality, customer loyalty, and perceived value in Malang GO-JEK drivers who use the Telkomsel Ojek Online Package in 2019, (2) to explain the direct effect of service quality on perceived value, and (3) to explain the direct and indirect influence on customer loyalty in GO-JEK drivers on Malang City who use prepaid Telkomsel Online Ojek Packages.